TEACHER’S LEADERSHIP COMPETENCY IN MANAGING ONLINE INSTRUCTION DURING THE PANDEMIC DISRUPTION IN INDONESIA - Sudarmo Sudarmo; Muslimah Muslimah (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2020)
Since COVID-19 shocked the world, all business activities experienced an enormous impact, including in the field of education. UNESCO advised the world to ease the pandemic's impact on world education continuity with distance learning policies to overcome this disruption. Since then, pandemic affected countries experienced difficulties implementing that distance learning to respond to the policy. In this regard, this paper was carried out to identify additional instructional leadership competencies for teachers in managing learning in a pandemic. Evidence from the study of education shows that learning in disruption time is closely related to teachers' management in innovating such high technological virtual learning. To find answers, we conducted preliminary readings of the relevant literature. Next, we analyzed that information qualitatively by exploring what teacher instruction management is applicable during the pandemic. Then, we found that additional teaching leadership competencies can be adopted to support students learning in virtual approaches such as reflective opportunities, increasing truth among teachers and students, keeping curiosity habits, building productive communication, initiative habit, and more listening to understand others. Those additional teaching leadership competencies are useful to any party interested in supporting students learning in the pandemic disruption.